2009, No. 4, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Rasa Zabarauskaitė, Poverty line calculation in the middle-income countries: methodological approach, 9 Romualdas Valkauskas, Factorial index analysis in the research of change in expressions, 17 Kirilas Kundušas, Živilė Simonaitytė, International financial reporting standards and USA accounting principles: main differences, their causes and convergence, 25 Monika Juonytė, Inga Galvanauskaitė, 7th International Financial Reporting Standard‘s „Cash Flow Reports“ and 5th Business Accounting Standard‘s „Cash Flow Report“ comparative analysis, 37 Anastasija Jankauskaitė, Vilma Jelisejevaitė, Business combination accounting, 52 Dainius Masiulevičius, Rasa Aleliūnaitė, Comparative analysis of 19th business accounting standard „Provisions, contingent liabilities, and contingent assets and events after the balance sheet date“ and 37th international accounting standard „Provisions, contingent liabilities, and contingent assets“, 66 Eglė Grūnovaitė, The impact of currency exchange rate difference on financial results, 82 Jokūbas Leipus, Gilmintas Albertavičius, Financial institutions of Islamic countries and their accounting features, 92 Marija Kučinskienė, Asta Fominienė, The benefit of business incubators when stimulating the development of small and medium enterprises, 102 Daiva Raziūnienė, New accounting textbook, 113